2013
DOI: 10.1007/s00432-013-1412-6
|View full text |Cite
|
Sign up to set email alerts
|

MG132-mediated inhibition of the ubiquitin–proteasome pathway ameliorates cancer cachexia

Abstract: Our results demonstrate that MG132-induced inhibition of the ubiquitin-proteasome pathway in cancer cachexia decreased the activity of NF-κB and the degradation of IκBα, and reduced the levels of TNF-α and IL-6 in serum and gastrocnemius tissue, accompanied by downregulation of MuRF1 and MAFbx. These data suggest that MG132 is a potential therapeutic and preventive agent for cancer cachexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 38 publications
(40 reference statements)
2
50
1
Order By: Relevance
“…In contrast with the results shown in the present study, treatment with a different proteasome inhibitor, namely MG132, has been reported to attenuate body weight loss and muscle depletion in mice bearing the C26 colon adenocarcinoma . Such a discrepancy could rely on the fact that MG132 does not just inhibit proteasome, but also cathepsins and calpains .…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with the results shown in the present study, treatment with a different proteasome inhibitor, namely MG132, has been reported to attenuate body weight loss and muscle depletion in mice bearing the C26 colon adenocarcinoma . Such a discrepancy could rely on the fact that MG132 does not just inhibit proteasome, but also cathepsins and calpains .…”
Section: Discussioncontrasting
confidence: 99%
“…Deletion of the TRAF6 reduced the expression of the muscle-specific ubiquitin ligases MuRF1 and MAFBx (18), which are critical proteins in the development of muscle atrophy (41,42). We further inferred that MAFBx and MuRF1 may be upregulated in denervated TA muscle.…”
Section: Discussionmentioning
confidence: 80%
“…These two E3 ubiquitin ligases have been heavily studied and regarded as a primary cause of wasting in cachexia. Treatment with the proteasome inhibitor MIG132 has been shown to alleviate cachexia by inhibiting MAFBx and MuRF-1, showing their involvement in wasting (44). The wasting phenotype does not involve a reduction in the total number of muscle fibers or altered force generation per unit of cross-sectional area (25,29), although others have reported a significant reduction of force/cross-sectional area in the murine C26 model (28) and in human patients (38).…”
Section: Discussionmentioning
confidence: 99%